Ecology and Conservation of Tropical Marine Faunal Communities 2013
DOI: 10.1007/978-3-642-38200-0_25
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Recovery of Bleached Corals in Andaman: Fishes as Indicators of Reef Health

Abstract: The corals in Andaman and Nicobar Islands suffered extensive bleaching during April 2010 to the extent of 60-70 % due to elevated sea surface temperature (SST) and a significant portion of that is hitherto dead. This study evaluates the degree of recovery of the coral reefs and reef fishes, a year after the event. Line intercept transect (LIT) surveys were conducted in three sites, namely, North Bay, Tarmugli and Chidiyatapu for assessing coral cover together with visual census of reef fishes along the same tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Unfortunately, a direct comparison between grouping before and after the bleaching event is not possible, since no data are available on mixed-grouping in fishes from these regions before the bleaching event. However, after the 1998 mass-bleaching event, studies reported roving mixed-groups of herbivores in both Lakshadweep and the Andaman Islands [22,32], although the species composition of these groups was not documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, a direct comparison between grouping before and after the bleaching event is not possible, since no data are available on mixed-grouping in fishes from these regions before the bleaching event. However, after the 1998 mass-bleaching event, studies reported roving mixed-groups of herbivores in both Lakshadweep and the Andaman Islands [22,32], although the species composition of these groups was not documented.…”
Section: Discussionmentioning
confidence: 99%
“…The death of corals can also lead to a reduction in the structural complexity of the reefs, eliminating shelter, which can affect the intensity of predation pressure and competition [17][18][19]. Generally, the higher trophic guilds and corallivorous fishes are most susceptible to decline in these situations [20] and herbivores tend to increase in abundance, probably owing to an increase in the algal cover [20][21][22]. Whether mixed-species grouping in herbivorous reef fishes is influenced by these changes or not remains unknown.…”
Section: Introductionmentioning
confidence: 99%